Desires under Reform: Contemporary Reconfigurations of Family, Marriage, Love and Gendering in a transnational South Indian Matrilineal Muslim community - Caroline Osella
I trace here some connections between contemporary reconfigurations of gendering, family and marriage in a matrilineal Muslim south Indian community (Kerala Koyas). I argue that shifts from joint matrifocal households to small neo-patriarchal households are underscored by market reforms, migration processes, Islamic reformism, and by modernist processes which work towards purging queer forms of affect and gender in favour of impeccably gendered heterosexual subjectivities. But I also note considerable ambivalence and tension within these moves, and argue against any teleological mappings of such moves which would - firstly - take for granted and - then - celebrate a shift from Indian ‘arranged marriage’ towards a ‘pure relationship’, founded on romantic and passionate love. Here, I engage with recent academic discussions of Western marriage, Indian middle class and Indian subaltern marriages, and conclude that many commonly drawn oppositions (‘love’ versus ‘arranged’, ‘companionate’ versus ‘ economic- pragmatic’, ‘till death us do part’ versus ‘easy divorce’) are representational fictions requiring sharp critique. I also address the question of moral panic around female centred households and proffer feminist and queer critiques. Finally, I build upon work by Saba Mahmood and others who are urging Western academics to examine their own production as liberal subjects.